The Acculturation Crisis and Religious Commodification in the Customary Conflict of Rencong Telang Kerinci - Ahmad, Jafar; Iskandar, Nuzul (JURNAL PENELITIAN, 2022)
This study examines the role and position of religion in the Rencong Telang customary conflict in Kerinci Regency, Jambi, which has led to the dualism of customary institutions and the commodification of religious symbols. The research highlights two key concerns: first, the crisis of acculturation between Islam and local traditions; and second, the instrumentalization of religion as a commodity in power contestations. Employing a qualitative approach, this study collects data through in-depth interviews, participant observations, and document analysis, which are subsequently analyzed using an interpretive-descriptive method. The findings reveal that the customary conflict in Rencong Telang emerged as a consequence of the declining authority of religious institutions, rendering them incapable of functioning as mediators in resolving social disputes. This crisis threatens the long-established integration of Islam and adat, embodied in the philosophy of adat bersendi syara’, syara’ bersendi Kitabullah. Moreover, in the absence of religious authority, Islamic values are increasingly commodified as a tool for gaining influence and legitimacy in customary disputes. This research contributes to the academic discourse on religious acculturation by offering a critical perspective on the vulnerability of religious institutions in conflict situations. Future studies should explore the broader socio-political implications of religious commodification and its impact on indigenous cultural resilience.